Analisis Pengaruh Kepemimpinan Transformasional, Kualitas Kehidupan Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan Pt. Eksekutif Media Utama Di Deli Serdang - Sutrisno, Brilliant Sutrisno; Rizal, Muhammad (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2024)
This study aims to describe the effect of transformational leadership, quality of work life, organizational culture on employee performance at PT Eksekutif Media Utama in Deli Serdang. This research was conducted for 4 (four) months, start from May 2022 until August 2022. This research use non probability sampling method. The respondents of this research are all employee at PT Eksekutif Media Utama in Deli Serdang which amounted to 89 (eighty nine) employees. The instrument of this research is a questionnaire to collent data from transformational leadership variable, quality of work life variable, organizational culture variable and employee performance variable. Data analysis techniques used are validity test, reliability test, descriptive analysis, multicolinearity test, normality test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test ot t test, simultaneous hypothesis test or F test, and calculation of coefficient of determination. The result of descriptive analysis for from transformational leadership variable, quality of work life variable, organizational culture variable and employee performance variable are in the good category at PT Eksekutif Media Utama in Deli Serdang. Based on partial analysis, transformational leadership, quality of work life, organizational culture have a positive and significant effect on employee performance at PT Eksekutif Media Utama in Deli Serdang. Simultaneously, transformational leadership, quality of work life, organizational culture have a positive and significant influence on employee performance at PT Eksekutif Media Utama in Deli Serdang. The contribution of transformational leadership, quality of work life, organizational culture variable to improve the employee performance variable is 0,785 or 78,5%, while rest of 0,215 or 21,5% influenced by other variables not examined by writer in this research, such as work satisfaction, work motivation, compensation and working environment.